Dissipative waves in real gases. (October 2017) - Gupta, Neelam; Sharma, V.D.
Abstract: In this paper, we characterize a class of solutions to the unsteady 2-dimensional flow of a van der Waals fluid involving shock waves, and derive an asymptotic amplitude equation exhibiting quadratic and cubic nonlinearities including dissipation and diffraction. We exploit the theory of nonclassical symmetry reduction to obtain some exact solutions in the limit of vanishing dissipation. Because of the nonlinearities present in the evolution equation, one expects that the wave profile will eventually encounter distortion and steepening which in the limit of vanishing dissipation culminates into a shock wave; and once shock is formed, it will propagate by separating the portions of the continuous region. Here we have shown how the real gas effects, which manifest themselves through the van der Waals parameters a ̃ and b ̃ influence the wave characteristics, namely the shape, strength, and decay behavior of shocks. Highlights: A class of solutions to the unsteady 2-dimensional flow of a real gas are studied. An asymptotic equation exhibiting quadratic and cubic nonlinearities is derived. Some exact solutions are obtained in the limit of vanishing dissipation. In the limit of vanishing dissipation wave profile culminates into shock wave. Wave characteristics, namely the shape, strength, and decay behavior of shocks are significantly influenced by van der Waals parameters 'a' and 'b'.